The role of cardiac biomarkers and epicardial fat in the diagnosis of heart failure in patients with various types of atrial fibrillation - D. V. Losik; E. V. Fisher; I. L. Mikheenko; N. A. Nikitin; S. M. Minin; V. V. Beloborodov; A. B. Romanov (Российский кардиологический журнал, 2022)
Aim. To assess the level of various cardiac biomarkers and the volume of epicardial adipose tissue (EAT) in patients with heart failure (HF) depending on the type of atrial fibrillation (AF).Material and methods. This prospective observational study included 69 patients with symptomatic AF, as well as with manifestations of New York Heart Association (NYHA) class II-III HF. All patients were examined before catheter ablation for AF. The following investigations were performed: echocardiography, computed tomography, myocardial perfusion scintigraphy, immunochemical analysis of cardiac biomarkers (brain natriuretic peptide (BNP), high-sensitivity troponin I (hs-TnI)), as well as biochemical analysis of high-sensitivity C reactive protein (hsCRP). Patients were divided into 2 groups, depending on the AF type, into paroxysmal and non-paroxysmal (persistent and long-standing persistent).Results. The analysis included 69 patients with various AF types and symptomatic HF. There were significantly more patients with HF confirmed by an elevated BNP level in the group with non-paroxysmal type (27 (71%) vs 5 (16%), p<0,00001). Comparison analysis showed that in group 2 the mean BNP level was significantly higher than in group 1 (135,5 pg/ml [75,2;303,2] vs 40 pg/ml [20,7;56,9], respectively, p<0,00001). The hs-TnI level was higher in group 2 (2,5 [1,7;5,1] vs 1,9 [0,8;3,9], respectively, p=0,19), but there was no significant difference between the groups. The level of hsCRP did not differ in both groups. In group 1, the EAT volume was 139 [117,5;171] vs 169 [130;209,5] in group 2 (p=0,03).Conclusion. The type of AF plays a role in the interpretation of cardiac specific enzymes, and BNP levels and EAT volume are higher in patients with the non-paroxysmal form.